Ab-initio investigation of the structural, electronic and optical properties of lead-free halide Cs2TiI6 double perovskites. (October 2020) - Natik, A.; Abid, Y.; Moubah, R.; Abid, M.; Lassri, H.
Abstract: We investigate the structural, electronic and optical properties of lead-free halide Cs2 TiI6 halide perovskites using ab -initio calculations. It is shown that the Ti-based halide perovskites possess several interesting properties, including high stability, suitable bandgap, and excellent optical absorption. It is demonstrated that the Cs2 TiI6 compound presents a bandgap energy value of 0.998 eV. The absorption coefficient is in the order of 10 5  cm −1, these properties make Cs2 TiI6 halide perovskites a good candidate for photovoltaic applications. In addition, the effect of pressure on the electronic properties were studied, in which we demonstrate that the bandgap energy depend significantly on the applied pressure. Highlights: The structural, electronic and optical properties of Cs2 TiI6 halide perovskites were studied. Cs2 TiI6 was found to possess several interesting properties, including high stability, suitable bandgap, and excellent optical absorption. The bandgap energy value is 0.998 eV and the absorption coefficient is in the order of 10 5  cm −1 . The effect of pressure on the electronic properties were studied.